Molecular Neuroimaging of the Dopamine Transporter as a Patient Enrichment Biomarker for Clinical Trials for Early Parkinson's Disease. Issue 3 (18th March 2019) - Romero, Klaus; Conrado, Daniela; Burton, Jackson; Nicholas, Timothy; Sinha, Vikram; Macha, Sreeraj; Ahamadi, Malidi; Cedarbaum, Jesse; Seibyl, John; Marek, Kenneth; Basseches, Peter; Hill, Derek; et al.
Abstract : The Critical Path for Parkinson's (CPP) Imaging Biomarker and Modeling and Simulation working groups aimed to achieve qualification opinion by the European Medicines Agency (EMA) Committee for Medical Products for Human Use (CHMP) for the use of baseline dopamine transporter neuroimaging for patient selection in early Parkinson's disease clinical trials. This paper describes the regulatory science strategy to achieve this goal. CPP is an international consortium of three Parkinson's charities and nine pharmaceutical partners, coordinated by the Critical Path Institute.